Home Algebra • Algebra and number theory, U Glasgow notes by Baker.

Algebra and number theory, U Glasgow notes by Baker.

By Baker.

Show description

Read Online or Download Algebra and number theory, U Glasgow notes PDF

Best algebra books

Squares (London Mathematical Society Lecture Note Series, Volume 171)

This paintings is a self-contained treatise at the study performed on squares via Pfister, Hilbert, Hurwitz, and others. Many classical and smooth effects and quadratic types are introduced jointly during this publication, and the therapy calls for just a simple wisdom of earrings, fields, polynomials, and matrices.

An Introduction to the Theory of Algebraic Surfaces

Zariski presents a superior creation to this subject in algebra, including his personal insights.

Additional info for Algebra and number theory, U Glasgow notes

Sample text

How many distinguishable regular tetrahedral dice can be made where each face has one of the numbers 1,2,3,4 on it? Here two such dice are deemed to be indistinguishable if one can be obtained from the other by a rotation. What about if we allow arbitrary symmetries between indistinguishable such dice? CHAPTER 3 Arithmetic functions 1. Definition and examples of arithmetic functions Let Z+ = N0 −{0} be the set of positive integers. A function ψ : Z+ −→ R (or ψ : Z+ −→ C) is called a real (or complex) arithmetic function if ψ(1) = 1.

Before showing how this result allows us to determine some concrete examples, we give a generalization. 15. Let X and Y be sets and suppose that Y has a subset Z ⊆ Y which admits a bijection g : Z −→ P(X). Then there is no surjection X −→ Y . Proof. Suppose that f : X −→ Y is a surjection. Choosing any element p ∈ P(X) and defining the function H : X −→ P(X); h(x) = g(f (x)) if f (x) ∈ Z, p if f (x) ∈ / Z, we easily see that h is a surjection, contradicting Russell’s Paradox. Thus no such surjection can exist.

We need the following facts. i) For x, y ∈ G, xH ∩ yH = ∅ ⇐⇒ xH = yH. This is seen as follows. If xH = yH then xH ∩ yH = ∅. Conversely, suppose that xH ∩ yH = ∅. If yh ∈ xH for some h ∈ H, then x−1 yh ∈ H. For k ∈ H, x−1 yk = (x−1 yh)(h−1 k), which is in H since x−1 yh, h−1 k ∈ H and H is a subgroup of G. Hence yH ⊆ xH. Repeating this argument with x and y interchanged we also see that xH ⊆ yH. Combining these inclusions we obtain xH = yH. ii) For each g ∈ G, |gH| = |H|. If gh = gk for h, k ∈ H then g −1 (gh) = g −1 (gk) and so h = k.

Download PDF sample

Rated 4.35 of 5 – based on 13 votes